Meningkatkan Kepedulian Masyarakat Pada Alam di Desa Tabing Rimbah Kabupaten Barito Kuala - Sitanggang, Ribka; Hidayah, Sri; Pramesti, Alifia Shindy; Riski , Ahmad Sawban; Ajam, Ajam; Anggraini, Ginawati Widya; Putra, Muhammad; Fitri, Noor (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Tabing Rimbah Village is located in Mandastana Sub-district, Barito Kuala Regency. This village has an advantage in agriculture, especially rice and citrus commodities. Therefore, the majority of the Tabing Rimbah community are farmers. However, since the floods that inundated the agricultural land, the Tabing Rimbah community can no longer grow oranges. One of the factors that exacerbated the impact of the flood disaster that occurred was the problem of waste. So that the waste problem became the concern of the service team. Basically, the waste problem is caused by the lack of garbage bins, which leads to bad actions by the community by littering. The solution that is encouraged to overcome the waste problem is the provision of garbage bins at 10 points in Tabing Rimbah Village that are easily accessible to the community. In addition to the provision of waste basket facilities, social aspects are also a concern in this service program. The activities carried out in this service program include socialization of waste utilization counseling, making trash bins and signs, and cleaning and renovating village parks. The implementation of activities was carried out from July 16 to August 21, 2023. The activities designed can be carried out well by involving the community to participate and fully participate in the various activities carried out. This program is directly able to foster community awareness of the environment, as well as increase community capacity in the utilization of used waste. Thus the achievements of this program are able to contribute to solving the problems faced by Tabing Rimbah Village, and the benefits can be felt by various levels of the Tabing Rimbah Village community.